Expressive Speech Acts in the Comments Column of Erick Thohir's Tiktok Account - Marsela, Jeny; Asnawi, Asnawi (Universitas Negeri Semarang, 2024)
The aim of this research is to describe expressive speech in writing through the comments column of the Tiktok account @Erick Thohir. This research uses qualitative research using descriptive methods. The data source in this research is attached through documentary evidence in the form of screenshots of findings from comments obtained in Erick Thohir's Tiktok account post with the topic